Impacts of macroeconomic variables on the stock market index in Poland: new evidence - Hsing, Yu; Hsieh, Wen-jen (Journal of Business Economics and Management, 2012)
Applying the GARCH or ARCH model, this paper finds that Poland’s stock market index is positively associated with industrial production or real GDP and the German stock market index, negatively affected by the government borrowing/GDP ratio, the real interest rate, the nominal effective exchange rate, the expected inflation rate, and the government bond yield in the euro area, and exhibits a quadratic relationship with the M2/GDP ratio. It suggests that the stock market index and the M2/GDP ratio show a positive (negative) relationship if the M2/GDP ratio is less (greater) than the critical value of 43.68%. Hence, to maintain a healthy stock market, the Polish authorities are expected to pursue economic growth, reduce government borrowing, avoid currency appreciation, and keep a relatively low interest rate or a relatively low expected inflation rate. Although currency appreciation has a negative impact on the stock market index, it is possible that the negative relationship might change if a certain threshold value is reached in the future.